2012
DOI: 10.1111/j.1096-0031.2012.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

On the phylogeny and evolution of Mesozoic and extant lineages of Adephaga (Coleoptera, Insecta)

Abstract: The relationships of extant and extinct lineages of Adephaga were analysed formally for the first time. Emphasis is placed on the aquatic and semiaquatic groups and their evolution in the Mesozoic. †Triadogyrus and †Mesodineutus belong to Gyrinidae, the sister group of the remaining families. †Triaplidae are the sister group of the following groups (Haliplidae, Geadephaga, Dytiscoidea incl. †Liadytidae, †Parahygrobiidae and †Coptoclavidae [major part]). The lack of a ventral procoxal joint and a very short pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 35 publications
(54 reference statements)
5
91
0
Order By: Relevance
“…A subdivision of Dytiscoidea into clades comprising Noteridae + Meruidae and the remaining groups is in agreement with previous studies (e.g. Balke et al ., ; Beutel et al ., ). In contrast, a sister‐group relationship between Dytiscidae and a clade containing the three small families Hygrobiidae, Aspidytidae and Amphizoidae, as recovered here, is a novel and unorthodox result.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A subdivision of Dytiscoidea into clades comprising Noteridae + Meruidae and the remaining groups is in agreement with previous studies (e.g. Balke et al ., ; Beutel et al ., ). In contrast, a sister‐group relationship between Dytiscidae and a clade containing the three small families Hygrobiidae, Aspidytidae and Amphizoidae, as recovered here, is a novel and unorthodox result.…”
Section: Resultsmentioning
confidence: 97%
“…However, these are likely to represent plesiomorphic character states (at least the transverse suture) retained from the groundplan of Dytiscoidea (e.g. Beutel et al ., ). Interestingly, a re‐examination of larval features has revealed that the larva of the Chinese species is strikingly similar to those of Amphizoidae, even though A. niobe is recovered as closer to Amphizoa in the analyses of combined or the mitochondrial DNA data (not so in the analyses of nuclear genes, where S. wrasei is sister to Amphizoidae).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The systematic position of the family within the suborder Adephaga is not fully settled (e.g., McKenna et al., ). However, a sister group relationship with all other adephagan families appears most likely, supported by morphological characters (Beutel & Roughley, ; Beutel et al., ) and also by a recent molecular study (Baca, Alana, Gustafson, & Short, ).…”
Section: Introductionmentioning
confidence: 85%
“…10 1 ). A representative species of the family Trachypachidae, regarded as the sister taxon of Carabidae in previous works (Erwin 1985, Beutel 1998, Kavanaugh 1998, RoigJuñent 1998, was used to root the tree.…”
Section: Cladistic Analysesmentioning
confidence: 99%